Konsep Ammah Menurut Nawawi Al-Bantani Serta Relevansinya Dengan Kesetaraan Gender - Masfufah, Latifatul; Maimun, Maimun; Zikri, Zikri (Universitas Sang Bumi Ruwa Jurai, 2025)
In this study, the philosophical basis of Nawawi al-Bantani's book Uqūd al-Lujayn will be analyzed. This book places the husband-wife relationship within a patriarchal framework and typically refers to the wife as a